Integrative Analysis of Metabolome and Transcriptome Identifies Potential Genes Involved in the Flavonoid Biosynthesis in Entada phaseoloides Stem - Lin, Min; Zhou, Zhuqing; Mei, Zhinan (Frontiers in Plant Science, 2022)
Entada phaseoloides stem is known for its high medicinal benefits and ornamental value. Flavonoids are one of the main active constituents in E. phaseoloides stem. However, the regulatory mechanism of flavonoids accumulation in E. phaseoloides is lacking. Here, phytochemical compounds and transcripts from stems at different developmental stages in E. phaseoloides were investigated by metabolome and transcriptome analysis. The metabolite profiling of the oldest stem was obviously different from young and older stem tissues. A total of 198 flavonoids were detected, flavones, flavonols, anthocyanins, isoflavones, and flavanones were the main subclasses. The metabolome data showed the content of acacetin was significantly higher in young stem and older stem than oldest stem. Rutin and myricitrin showed significantly higher levels in the oldest stem. A total of 143 MYBs and 143 bHLHs were identified and classified in the RNA-Seq data. Meanwhile, 34 flavonoids biosynthesis structural genes were identified. Based on the expression pattern of structural genes involved in flavonoids biosynthesis, it indicated that flavonol, anthocyanin, and proanthocyanin biosynthesis were firstly active during the development of E. phaseoloides stem, the anthocyanin/ proanthocyanin biosynthesis branch was dominant; the flavone biosynthesis branch was active at the late developmental stage of the stem. Through correlation analysis of transcriptome and metabolome data, the potential candidate genes related to regulating flavonoids synthesis and transport were identified. Among them, the MYBs, bHLH, and TTG1 co-regulated biosynthesis of flavonols and structural genes, bHLH and transporter genes co-regulated biosynthesis of anthocyanins. In addition, the WDR gene TTG1-like (AN11) may regulate dihydrochalcones and flavonols biosynthesis in specific combinations with IIIb bHLH and R2R3MYB proteins. Furthermore, the transport gene protein TRANSPARENT TESTA 12-like gene positively regulated the accumulation of rutin, the homolog of ABC transporter B family member gene positively correlated with the content of flavone acacetin. This study offered candidate genes involved in flavonoids biosynthesis, information of flavonoid composition and characteristics of flavonoids accumulation, improved our understanding of the MYBs and bHLHs related regulation networks of flavonoids biosynthesis in E. phaseoloides stem, and provided references for the metabolic engineering of flavonoids biosynthesis in E. phaseoloides stem.